Multimodal imaging of nano-assembled microspheres loaded with doxorubicin and Cisplatin for liver tumor therapy - He, Yiwei; Zhang, Yuqing; Gong, Yuanchuan; Zhang, Zhewei; Xu, Tiancheng; Tian, Liqiang; Pan, Ting; Yang, Hong; Pan, Hao; Kou, Quanming; Wang, Hao; Shao, Guoliang (Frontiers in Bioengineering and Biotechnology, 2022)
Currently, clinically available drug-loaded embolic microspheres have some shortcomings, such as being invisible with standard medical imaging modalities and only being able to carry positively charged drugs. The visualization of drug-loaded microspheres is very important for real-time monitoring of embolic position to improve the therapeutic effect. Meanwhile, the visualization of microspheres can enable postoperative reexamination, which is helpful for evaluating the embolization area and guiding the subsequent treatment. In addition, microspheres capable of loading different charged drugs can increase the choice of chemotherapeutic drugs and provide more possibilities for treatment. Therefore, it is of great importance to explore drug-loaded microspheres capable of multimodal imaging and loading drugs with different charges for transarterial chemoembolization (TACE) treatment of liver tumors. In our study, we designed a kind of nano-assembled microspheres（NAMs） that can realize computer X-ray tomography (CT)/ magnetic resonance imaging (MRI)/Raman multimodal imaging, be loaded with positively and negatively charged drugs and test their imaging ability, drug loading and biological safety. The microspheres have strong attenuation performance for CT, high T2 relaxation for MRI and good sensitivity for surface enhanced Raman spectroscopy (SERS). At the same time, our microspheres can also load the positively charged drug, doxorubicin (DOX), and negatively charged drug Cisplatin. One gram of NAMs can hold 168 mg DOX or 126 mg Cisplatin, which has good drug loading and sustained-release capacity. Cell experiments also showed that the nano-assembled microspheres had good biocompatibility. Therefore, as multimodal developed drug loaded microspheres, nano assembled microspheres have great potential in TACE treatment of liver cancer.